Penguatan Kapasitas Masyarakat melalui Program Sinergi Perguruan Tinggi: Sebuah Pendekatan Berkelanjutan di desa Cimarga Kabupaten Sumedang - Dedi Mulyadi (Bandung Conference Series: Economics Studies, 2024)
Abstract. The joint implementation of One Village One Product (OVOP), stunting prevention, and digital literacy form the integral foundation for advancing the rural economy. With this holistic approach, rural communities can not only improve the production and marketing of local products, but also build healthy and competitive human capital, in line with the adaptation of the healthy and competitive, in line with adapting to the development of the digital era. This effort is not not only a long-term investment for rural progress, but also an important contribution to improving the welfare and to improving the overall welfare and sustainability of the national economy. Program KKN Thematic 3 with the theme "Independent Universities Gotong Royong Membangun Desa (PTMGRD)" is a real step in the synergy of universities in West Java in order to increase the capacity of rural communities for sustainable village development. Village communities for sustainable village development. Abstrak. Implementasi bersama One Village One Product (OVOP), pencegahan stunting, dan literasi digital membentuk fondasi integral untuk memajukan ekonomi pedesaan. Dengan pendekatan holistik ini, masyarakat pedesaan tidak hanya dapat meningkatkan produksi dan pemasaran produk lokal, tetapi juga membangun modal manusia yang sehat dan berdaya saing, sejalan dengan adaptasi terhadap perkembangan era digital. Upaya ini bukan hanya merupakan investasi jangka panjang untuk kemajuan pedesaan, melainkan juga merupakan kontribusi penting dalam meningkatkan kesejahteraan dan keberlanjutan ekonomi nasional secara keseluruhan. Program KKN Tematik 3 dengan tema “Perguruan Tinggi Mandiri Gotong Royong Membangun Desa (PTMGRD)” merupakan langkah nyata sinergitas perguruan tinggi di Jawa Barat dalam rangka peningkatan kapasitas Masyarakat desa untuk Pembangunan desa berkelanjutan.